Chapter Конфесионално-литургичке полемике у теолошким списима Зелићевих савременика - Vukašinović, Vladimir (Biblioteca di Studi Slavistici, 2019)
The works of Serbian theologians of the second half of the 18th century are characterized by a confessional-polemic style, as their goal was to set the sacred doctrine and the organization of liturgical life. This polemic approach was also due to the unfortunate position of the Orthodox minorities within the Austrian Monarchy, exposed as they were to the pressure of the Catholic Church. Analysing the works of the leading Serbian theologians of the time (D. Novaković, J. Rajić, Z. Orfelin), the author explains how Serbian polemical theology was created and eventually found its own formal style.